Pengaruh Penggunaan Aplikasi Game pada Smartphone terhadap Hasil Belajar Mahasiswa Program Studi PGSD STKIP PGRI Trenggalek - Anis Jannatul Firdausi; Efi Ika Febriandari; Angga Setiawan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
The purpose of this study is to find out whether there is an influence of the use of game applications on smartphones on the learning outcomes of PGSD STKIP PGRI Trenggalek student learning outcomes, by using quantitative research methods with non-experimental research types or Ex-postfacto. Data obtained by distributing questionnaires through google form with the aim to determine the effect of using game applications on smartphones (independent variables) and documentation to determine student learning outcomes (dependent variable). After the data is collected, it is analyzed by the simple linear regression hypothesis test. The result of analyzing the data it is known that there is a significant influence with the results of r count = 7.774 and consulted with the value of t table = 1.699 with a confidence level of 95%. While the influence of variable X (the use of game applications on smartphones) on the Y variable (learning outcomes) was 49.4%. With these results, the alternative hypothesis is accepted and the null hypothesis is rejected. In other words it can be concluded that there is a significant influence on the use of game applications on smartphones on the learning outcomes of PGSD STKIP PGRI Trenggalek student learning outcomes.